A novel extraction approach and unique physicochemical properties of gelatin from the swim bladder of sturgeon. (22nd November 2020) - Wang, Lin; Li, Peiyu; Ren, Yuhan; Bai, Fan; Wang, Jinlin; Zhang, Yuhao; Jin, Wengang; El‐Seedi, Hesham; Gao, Ruichang
Abstract: BACKGROUND: Gelatin is traditionally produced from mammals and widely applied in the food industry. The production is tedious, time‐consuming and environment‐unfriendly, while the application is restricted because of zoonosis risk and religious sentiment. RESULTS: Gelatin was extracted by hot water from sturgeon swim bladder after defatting with alcohol and hexane. The yield reached to 94.15% under the optimized conditions of 50 °C, 30 min and 10 mL g −1 . Its amino acid and subunit profiles were similar to type I collagen. Compared to commercial porcine, bovine and piscine gelatins, it exhibited higher whiteness (3.38), emulsion activity (171.76 m 2 g −1 ), gel strength (853.23 g), water‐holding capacity (92.37%) and viscoelasticity (0.03). But the transmittance (40.56% at 450 nm and 59.07% at 620 nm), emulsion stability (30.09 min), foam expansion (203.00) and stability (26.92), gelling (16.88 °C) and melting temperature (21.80 °C) were lower. While the pH (6.87) and viscosity (28.60 mPa s) were moderate. Moreover, it made better hydrogels and nanofibers. CONCLUSION: Gelatin was extracted from sturgeon swim bladder using a clean and efficient approach, and exhibited unique properties and great potential for the food industry. © 2020 Society of Chemical Industry